Cytotoxicity of Snake Venoms and Cytotoxins From Two Southeast Asian Cobras (Naja sumatrana, Naja kaouthia): Exploration of Anticancer Potential, Selectivity, and Cell Death Mechanism - Chong, Ho Phin; Tan, Kae Yi; Tan, Choo Hock (Frontiers in Molecular Biosciences, 2020)
Venoms of cobras (Naja spp.) contain high abundances of cytotoxins, which contribute to tissue necrosis in cobra envenomation. The tissue-necrotizing activity of cobra cytotoxins, nevertheless, indicates anticancer potentials. This study set to explore the anticancer properties of the venoms and cytotoxins from Naja sumatrana (Equitorial spitting cobra) and Naja kaouthia (monocled cobra), two highly venomous species in Southeast Asia. The cytotoxicity, selectivity and cell death mechanisms of their venoms and cytotoxins (NS-CTX from N. sumatrana: NS-CTX; N. kaouthia: NK-CTX) were elucidated in human lung (A549), prostate (PC-3) and breast (MCF-7) cancer cell lines. Cytotoxins were purified through a sequential fractionation approach using cation exchange chromatography, followed by C18 reverse-phase high-performance liquid chromatography to homogeneity validated with sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and identified by liquid chromatography-tandem mass spectrometry (LCMS/MS). The cobra venoms and their respective cytotoxins exhibited concentraion-dependent growth inhibitory effects in all cell lines tested, with the cytoxins being more potent compared to the corresponding whole venoms. NS-CTX and NK-CTX are, respectively, P-type and an S-type isoforms of cytotoxin, based on the amino acid sequences as per LCMS/MS analysis. Both cytotoxins exhibited differential cytotoxic effects in the cell lines tested, with NS-CTX (P-type cytotoxon) being significantly more potent in inhibiting the growth of the cancer cells. Both cytotoxins desmonstrated promising selectivity only for the A549 lung cancer cell line (selectivity index = 2.17 and 2.26, respectively) but not in prostate (PC-3) and breast (MCF-7) cancer cell lines (selectivity index < 1). Flow cytometry revealed that the A549 lung cancer cells treated with NS-CTX and NK-CTX underwent necrosis predominantly. Meanwhile, the cytotoxins induced mainly caspase-independent late apoptosis in the prostate (PC-3) and breast (MCF-7) cancer cells lines, but lacked selectivity. The findings revealed the limitations and challenges that could be faced during the development of new cancer therapy from cobra cytotoxins, notwithstanding their potent anticancer effects. Further studies should aim to overcome these impediments to unleash the anticancer potentials of the cytotoxins.